ANALISIS KRITIS TEKNIK INTERVIEW INTERNASIONAL DALAM REKRUTMEN DAN SELEKSI SUMBER DAYA MANUSIA PENDIDIKAN ISLAM DI ERA GLOBAL - Faujiyani; Edomi Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to critically analyze the implementation of international interview techniques in the recruitment and selection of human resources within Islamic educational institutions in the global era. The research employed a qualitative approach using a library research method. Data were collected from books, reputable journal articles, international organizational documents, and other relevant literature on human resource management, international interview techniques, and Islamic education. Data were analyzed using qualitative content analysis through the stages of data condensation, data display, and conclusion drawing. The findings indicate that international interview techniques, including structured interviews, behavioral interviews, competency-based interviews, situational interviews, and panel interviews, enhance the objectivity, transparency, and effectiveness of recruitment and selection processes. Nevertheless, their implementation faces challenges such as cultural bias, limited foreign language proficiency, digital technology disparities, and algorithmic bias. The study further reveals that international interview practices should be integrated with Islamic values, including amanah (trustworthiness), siddiq (honesty), tabligh (communicativeness), fathanah (wisdom), justice, and professionalism. As its scientific contribution, this research proposes the Islamic Global Interview Model (IGIM), which integrates professional competence, global cultural intelligence, integrity, Islamic character, and collaborative leadership as a conceptual recruitment model for Islamic educational institutions in the global era.